Metaphor is a productive way in the formation of medical terminology - Sherizatova, Zh.Zh. (Ye.A.Buketov Karaganda State University Publishing house, 2019)
In the article metaphorization as a way in the formation of medical terminology was analyzed. The main attention is paid to the structural and semantic analysis, the main thematic groups of metaphorical terms are highlighted here. On the basis of the semantic analysis on the main trends in the formation of metaphor terms in the medical field were revealed. Metaphorical transfer of names in the terminological system is noted regularly and is determined by the constant development of the formation of new names and meanings of medical terms through the scientific rethinking of well-known words. It is revealed that medical terms are characterized by metaphorical, holistic, generalized and figurative meaning, which are based on metaphorical rethinking resulting from associative and figurative thinking. Metaphorization is the most important and productive source of enrichment of the medical terminological foundation.
Метафора медициналық терминдердің ең нəтижелі тəсілі ретінде
Метафора как наиболее продуктивный способ образования медицинских терминов
Keywords: metaphorization; terminological system; terminological metaphor; medical terminology; semantics; structure